Avatar-User Bond as Meta-Cognitive Experience: Explicating Identification and Embodiment as Cognitive Fluency - Sah, Young June; Rheu, Minjin; Ratan, Rabindra (Frontiers in Psychology, 2021)
Scholars have not reached an agreement on a theoretical foundation that underlies the psychological effects of avatar use on users. One group of scholars focuses on the perceptual nature of avatar use, proposing that perceiving the self-being represented by a virtual representation leads to the effects (i.e., Proteus effect). Another group suggests that social traits in avatars prime users causing them to behave in accordance with the social traits (i.e., priming effects). We combine these two theoretical explanations and present an alternative approach, hinging on a concept of meta-cognitive experience. The psychological mechanism of the avatar-user bond is explicated in terms of cognitive fluency, a type of meta-cognitive experience reflecting an awareness of how readily or easily information is processed. Under this explication, two concepts related to avatar-user bond, identification and embodiment, are understood as the meta-cognitive experience of cognitive fluency at the level of one’s identity and physical body, respectively. Existing empirical evidence on avatar effects is revisited to explore how this new theoretical framework can be applied.